Meningkatkan keterampilan literasi informasi dalam pembelajaran sejarah menggunakan metode Double Loop Problem Solving (DLPS) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2021)
This research is motivated by the low information literacy skills of students in learning history. These indications can be seen from the ability to analyze the connectedness of historical events and the ability to process student information. Based on these problems, the researchers formulated the problem “how to improve information skills in history learning using the Double Loop Problem Solving (DLPS) method through E-Learning?. This study uses the research design of Kemmis and McTaggart, which includes planning, implementation, observation, and reflection. The researched aspects of information literacy skills are recognizing needed information, accessing relevant information, selecting and comparing information from different sources, evaluating appropriate information, organizing and using information efficiently, combining and constructing information into new knowledge, and communicating and reflecting information. Based on the results of research conducted, the use of Double Loop Problem Solving (DLPS) can improve students’ information literacy skills in learning history. In the first cycle, the average percentage is 50.4%, the second cycle is 60%, and the third cycle is 82.8%.
Keywords: Classroom action research; Double Loop Problem Solving (DLPS) method; information literacy skills; history learning